2016
DOI: 10.1177/0959683615622554
|View full text |Cite
|
Sign up to set email alerts
|

A new subfossil locality for the extinct large Malagasy eagle Stephanoaetus mahery (Aves: Falconiformes): Implications for time of extinction and ecological specificity

Abstract: We report on the second known locality for a large Malagasy eagle, Stephanoaetus mahery, that went extinct during the Holocene. This nearly complete skeleton comes from Ankilitelo Cave, a deep vertical pitfall shaft in the southwestern lowland portion of the island and in the subarid bioclimatic zone. The specimen was radiocarbon dated to 5550 ± 30 BP (Beta-415922). The holotype of this species comes from Ampasambazimba in the Central Highlands, part of the subhumid bioclimatic zone. The eagle remains from Ank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Madagascar's living vertebrates exhibit markedly reduced diversity relative to what existed even a few hundred years ago. The island's subfossil (Late Pleistocene and Holocene) record has contributed greatly to our understanding of Madagascar's recent ecological evolution, and aided interpretations of recent environmental change; this record includes large‐bodied lemurs, elephant birds, pygmy hippos, crocodyliforms, turtles, bats, carnivorans, rodents and the aardvark‐like Plesiorycteropus (Burney et al ., ; Godfrey et al ., , ; Gommery et al ., ; Goodman & Muldoon, ; Goodman et al ., ; Samonds, ). The arrival of humans, the timing of which is still under debate (Anderson et al ., ; Dewar et al ., ; Godfrey et al ., ; Hansford et al ., ; Pierron et al ., ), nevertheless pre‐dated the decline and extinction of many of them, including the island's large (> 10 kg) native animals; the megafaunal crash did not occur until sometime during the past two millennia (Burney et al ., ; Crowley, ; Godfrey et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Madagascar's living vertebrates exhibit markedly reduced diversity relative to what existed even a few hundred years ago. The island's subfossil (Late Pleistocene and Holocene) record has contributed greatly to our understanding of Madagascar's recent ecological evolution, and aided interpretations of recent environmental change; this record includes large‐bodied lemurs, elephant birds, pygmy hippos, crocodyliforms, turtles, bats, carnivorans, rodents and the aardvark‐like Plesiorycteropus (Burney et al ., ; Godfrey et al ., , ; Gommery et al ., ; Goodman & Muldoon, ; Goodman et al ., ; Samonds, ). The arrival of humans, the timing of which is still under debate (Anderson et al ., ; Dewar et al ., ; Godfrey et al ., ; Hansford et al ., ; Pierron et al ., ), nevertheless pre‐dated the decline and extinction of many of them, including the island's large (> 10 kg) native animals; the megafaunal crash did not occur until sometime during the past two millennia (Burney et al ., ; Crowley, ; Godfrey et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the remains recovered belong to smaller-bodied hawks, kites, and owls that would not be able to carry a quarry as large as Palaeopropithecus. However, remains of at least one extinct crowned eagle (Stephanoaetus mahery) have also been recovered from Ankilitelo (Goodman and Muldoon, 2016). This species was considerably larger than still-extant raptors, and likely larger than its living congener, the African crowned eagle, which regularly predates primates up to ca.…”
Section: Discussionmentioning
confidence: 99%
“… Map of Madagascar showing sites where Archaeolemur specimens used in this study were found. Ecoregions adapted from Goodman and Muldoon ( 2016 ). Range of dates for Ankarana sites from Simons et al ( 1995 ), Belo‐Sur‐Mer from Burney et al ( 2004 ), Ankilitelo cave from Muldoon et al ( 2009 ) …”
Section: Methodsmentioning
confidence: 99%